Medical Devices Monitoring Using RFID - Baharom, Muhammad Har A'izzat; Nur Ilyani Ramli (Evolution in Electrical and Electronic Engineering, 2023)
The Medical Devices Monitoring system is proposed to address the asset management issues encountered in government hospitals. These issues include the inability to accurately track the location and utilization of medical devices, which can result in inefficient resource management, delays in patient treatment, and the risk of medical errors. The proposed solution utilizes RFID technology to track and monitor medical devices in real time, improving asset management and contributing to patient safety. The system includes an RFID reader, which allows users to scan devices that have RFID tags when borrowing them. Real-time data on the utilization and performance of medical devices can be provided through RFID technology, allowing for effective resource management. Additionally, sophisticated monitoring features ensure responsible device usage, further enhancing patient safety. The proposed system was built using Arduino IDE, Google Spreadsheet, Apps script, RFID tags and readers, and Node MCU. Testing was conducted through test plans, user acceptance, and accuracy testing, and based on the testing results, the system was successfully implemented and is ready to be deployed. Despite limitations, future enhancements have been suggested to further improve asset management in healthcare facilities. In summary, the proposed Medical Devices Monitoring system offers an effective solution to address asset management issues encountered in government hospitals. The system utilizes RFID technology to track and monitor medical devices in real time, contributing to patient safety and optimizing resource management.